Production performance and water quality of Caulerpa lentillifera with fermented fruit vegetable fertilizer - Eddy Supriyono; Chrisliana Chrisliana; Yuni Puji Hastuti; Kadek Lila Antara; Yong Ee Ling; Wildan Nurussalam (Jurnal Akuakultur Indonesia)
The use of fermented vegetable and fruit waste (FVF) based fertilizers as an effort to reduce waste has the potential to be used to support aquaculture activities. This study aims to evaluate the effectiveness of Caulerpa lentillifera cultivation with the addition of fertilizer based on fruit and vegetable waste fermentation on water quality parameters and production performance. The experimental design used was a completely randomized design with three replications for four different doses of FVF fertilizer treatments, namely 0, 0.05, 0.1, and 0.2 µl/L. This study used an initial weight of 500 g which was reared in a concrete tank with a capacity of 1000 L for 30 days growth period. The results showed that the use of FVF of 0.1 µl/L gave a better net harvest weight (p<0.05), namely 0.08 ± 0.06 kg.